Pengendalian Persediaan Bahan Baku Coffe Shop Menggunakan Metode ABC Analisis Berbasis POM-QM For Windows 5.3 - Akmal, Fahrezi; Zaki , Muhammad; Aqmal, Muhammad; Pangastuti, Nova (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
In the era of globalization with intense business competition, managing inventory becomes a crucial factor in achieving optimal profits. This study uses POM-QM for Windows 5.3 software to solve production and operational management problems, and the ABC method helps focus management attention on the most important items in the inventory system. The results show that category A contributes 76.12% to the total inventory value. Items in category B contribute 16.04%, while items in category C contribute only 7.84%. The recommended management strategy includes strict control for category A, moderate control for category B, and minimal attention for category C. Continuous implementation and monitoring are necessary to ensure that inventory management strategies are effective and adaptable to changes in demand or market conditions. With this method, coffee shops can ensure the availability of raw materials, reduce storage costs, and improve overall operational efficiency.